Combined Bacteriophage and Antibiotic Treatment Prevents Pseudomonas aeruginosa Infection of Wild Type and cftr- Epithelial Cells - Luscher, Alexandre; Simonin, Juliette; Falconnet, Léna; Valot, Benoît; Hocquet, Didier; Chanson, Marc; Resch, Grégory; Köhler, Thilo; van Delden, Christian (Frontiers in Microbiology, 2020)
With the increase of infections due to multidrug resistant bacterial pathogens and the shortage of antimicrobial molecules with novel targets, interest in bacteriophages as a therapeutic option has regained much attraction. Before the launch of future clinical trials, in vitro studies are required to evaluate the efficacies and potential pitfalls of such therapies. Here we studied in an ex vivo human airway epithelial cell line model the efficacy of phage and ciprofloxacin alone and in combination to treat infection by Pseudomonas aeruginosa. The Calu-3 cell line and the isogenic CFTR knock down cell line (cftr-) infected apically with P. aeruginosa strain PAO1 showed a progressive reduction in transepithelial resistance during 24h. Administration at 6h p.i. of single phage, phage cocktails or ciprofloxacin alone prevented epithelial layer destruction at 24h p.i. Bacterial regrowth, due to phage resistant mutants harboring mutations in LPS synthesis genes, occurred thereafter both in vitro and ex vivo. However, co-administration of two phages combined with ciprofloxacin efficiently prevented PAO1 regrowth and maintained epithelial cell integrity at 72h p.i. The phage/ciprofloxacin treatment did not induce an inflammatory response in the tested cell lines as determined by nanoString® gene expression analysis. We conclude that combination of phage and ciprofloxacin efficiently protects wild type and cftr- epithelial cells from infection by P. aeruginosa and emergence of phage resistant mutants without inducing an inflammatory response. Hence, phage-antibiotic combination should be a safe and promising anti-Pseudomonas therapy for future clinical trials in particular for cystic fibrosis patients.